KAJIAN PERUBAHAN KARAKTER PRODUKSI TANAMAN KEDELAI (Glycine max (L.) Merrill) PADA LINGKUNGAN TERNAUNGI - Chairudin Chairudin (Universitas Teuku Umar, 2018)
Shade is one of the obstaclesin the cultivation of soybean crops in intercroppingsystems. This study aims to determine the change in the characters of agronomic and morpho-physiological leaves of soybean plants due to shade. This research was conducted at the experimental farm of Agriculture Faculty, Teuku Umar University Meulaboh in West Aceh, from August to November 2013. This study uses split plot design with three replications where separated sub plot (vareities: Anjasmoro, Kipas Merah Bireun, Grobogan, Burangrang, Sinabung, Kaba) nested in the mainplot (shade: without shade, 25% and 50% shade). The results showed that the shade and varieties very significant effected on changes in production characters except 100-seed weight. While the interaction shade and varieties very significant effect on changes in production characters except variables 100-seed weight.